Changing the Paradigm for the Treatment and Development of New Therapies for FSGS - Spino, Cathie; Jahnke, Jordan S.; Selewski, David T.; Massengill, Susan; Troost, Jonathan; Gipson, Debbie S. (Frontiers in Pediatrics, 2016)
Focal segmental glomerulosclerosis (FSGS) is a renal pathology finding that represents a constellation of rare kidney diseases which manifest as proteinuria, edema nephrotic syndrome, hypertension and increased risk for kidney failure. Therapeutic options for FSGS are reviewed displaying the expected efficacy from 25 to 69% depending on specific therapy, patient characteristics, cost, and common side effects. This variability in treatment response is likely caused, in part, by the heterogeneity in the etiology and active molecular mechanisms of FSGS. Clinical trials in FSGS have been scant in number and slow to recruit, which may stem, in part, from reliance on classic clinical trial design paradigms. Traditional clinical trial designs based on the “learn and confirm” paradigm may not be appropriate for rare diseases such as FSGS. Future drug development and testing will require novel approaches to trial designs that have the capacity to enrich study populations as well as adapt the trial in a planned way to gain efficiencies in trial completion timelines. A clinical trial simulation is provided that compares a classical and more modern design to determine the maximum tolerated dose in FSGS.